Učinkovitost državnih pomoči za reševanje in prestrukturiranje podjetij v Sloveniji - Murn, Ana (Naše gospodarstvo, 2009)
State aid for rescuing and restructuring belongs among the most theoretically contentious forms of assistance, as it represents aid to old industries that have experienced difficulties. The aid is only justified in terms of eliminating the negative market consequences of companies'' exiting the market and saving a large number of jobs. An analysis of the efficiency of state aid granted in 1998-2006 in Slovenia showed that 23.6% of aid recipients did not survive. Furthermore, in companies which did survive, aid proved ineffective in promoting sales, increasing productivity and creating new jobs.
Keywords: Slovenia; Slovenija; podjetja; prestrukturiranje; financiranje; državna pomoč; subvencije; učinkovitost; efficiency